The Greek version of shoulder rating questionnaire (SRQ): Translation, cultural adaptation, a reliability and validity study in patients with rotator cuff related shoulder pain. - Cheimonidou, Areti Zoe; Stergioulas, Apostolos; Lamnisos, Demetris; Galanis, Petros; Stasinopoulos, Dimitrios (Physiotherapy Theory & Practice, 2023)
The Shoulder Rating Questionnaire (SRQ) was created in the English language to assess shoulder disorders in six areas: global function, pain, daily activities, recreational and athletic activities, and work. The study aimed to translate and culturally adapt Shoulder Rating Questionnaire (SRQ) into Greek. The SRQ English version was translated and adapted into the Greek language using forward translation, expert panel synthesis, and backward translation procedures. A pilot testing has been made in the target population, and the final version was created. A cross-sectional study was conducted in clinical settings with the SRQ and the Shoulder Pain and Disability Index. A total of 168 Greek adult patients with rotator cuff-related shoulder pain were recruited from physical therapy clinics. Τhe reliability of the SRQ Greek version was assessed using intraclass correlation coefficients. Internal consistency was assessed using the Cronbach alpha coefficient. Concurrent validity was measured by correlating the Shoulder Rating Questionnaire with the Shoulder Pain and Disability Index using Pearson's correlation coefficient. The results showed that the SRQ Greek version has excellent internal consistency (Cronbach's α = 0.99), test–retest reliability (ICC = 0.976), and concurrent validity (r > 0.9). No ground or ceiling effects were found. The standard error of measurement and the minimum detectable change of the total score were 5.55 and 15.38. The Greek Language Version of the SRQ is a reliable and valid instrument that can be used to evaluate adult patients with shoulder rotator cuff-related disorders in the acute or chronic phases and in clinical trials.